Role of Surfactant Protein D in Experimental Otitis Media - Osama Abdel-Razek; Tianyi Liu; Xinghua Chen; Qiushi Wang; Gautam Vanga; Guirong Wang (Karger Publishers, 2021)
Surfactant protein D (SP-D) is a C-type collectin and plays an important role in innate immunity and homeostasis in the lung. This study studied SP-D role in the nontypeable Haemophilus influenzae (NTHi)-induced otitis media (OM) mouse model. Wild-type C57BL/6 (WT) and SP-D knockout (KO) mice were used in this study. Mice were injected in the middle ear (ME) with 5 μL of NTHi bacterial solution (3.5 × 105 CFU/ear) or with the same volume of sterile saline (control). Mice were sacrificed at 3 time points, days 1, 3, and 7, after treatment. We found SP-D expression in the Eustachian tube (ET) and ME mucosa of WT mice but not in SP-D KO mice. After infection, SP-D KO mice showed more intense inflammatory changes evidenced by the increased mucosal thickness and inflammatory cell infiltration in the ME and ET compared to WT mice (p < 0.05). Increased bacterial colony-forming units and cytokine (IL-6 and IL-1β) levels in the ear washing fluid of infected SP-D KO mice were compared to infected WT mice. Molecular analysis revealed higher levels of NF-κB and NLRP3 activation in infected SP-D KO compared to WT mice (p < 0.05). In vitro studies demonstrated that SP-D significantly induced NTHi bacterial aggregation and enhanced bacterial phagocytosis by macrophages (p < 0.05). Furthermore, human ME epithelial cells showed a dose-dependent increased expression of NLRP3 and SP-D proteins after LPS treatment. We conclude that SP-D plays a critical role in innate immunity and disease resolution through enhancing host defense and regulating inflammatory NF-κB and NLRP3 activation in experimental OM mice.